Determinants of digital technologies adoption in government census data operations - Ofosu-Ampong, Kingsley; Asmah, Alexander; Kani, John Amoako; Bibi, Dzifa (Digital Transformation and Society, 2023)
PurposeThis study investigates the determinants of digital census for population and housing census (PHC) program through the lens of performance expectancy, technology readiness, self-efficacy and hedonic motivation for the upliftment of a national data collection exercise and development of human resource management.Design/methodology/approachA quantitative and qualitative research method was used to survey enumerators' responses from the PHC exercise during the COVID-19 period in Ghana. Based on the four determinants, a conceptual framework was developed consisting of eight proposed hypotheses tested through a structural equation model.FindingsThe findings of the study indicate that technological readiness, self-efficacy and hedonic motivation significantly influence behavioural intention to adopt digital technologies for PHC training and data collection. Importantly, the authors identified four key themes relating to digital technologies in PHC – personal enablers, general enablers, inherent affordances (inherent possibilities by the user in relation to what the technology offers in context) and personal inhibitors.Originality/valueFor research, this work systematizes antecedents from diverse research streams and validates their relative impact on government digital transformation for accurate data, thus providing a cohesive theoretical explanation of digital technologies in PHC. Due to the study's infancy in a developing country context, the findings provide a preliminary foundation and constructive insight for a digitalization plan conducive to people’s personality and technological readiness.